Applying Systems Thinking Concepts to Major Casualty Fires: Lessons Learned from Taiwan - Wen-Yen Juan; Wei-Sheng Chen; Chia-Lung Wu (Fire)
At 2:54 A.M. on 14 October 2021, a devastating fire erupted in a high-rise building in Kaohsiung City, Taiwan, involving 12 floors above ground and a basement level, resulting in 46 fatalities and 41 injuries. The official investigation pinpointed regulatory deficiencies and negligence among relevant department officials. The persistence of major fires globally underscores that merely relying on post-incident investigation reports is insufficient to fully uncover the underlying problems, highlighting the complexity of fire-related systemic challenges. This study adopts a systems thinking approach and synthesizes findings from various sources, including the investigation reports of this fire and the Grenfell Tower fire, research on fatal fires, and literature on high-rise building fires. It examined the systemic issues related to fires from three angles: resident characteristics, building factors, and situational factors. The analysis exposes the deep complexity of fire-related systemic problems and the interconnections among various contributing elements. Comprehensive initiatives that span educational, legislative, policy, and economic domains must be launched to reduce the frequency of fires and enhance survival rates. The insights from this study offer a profound understanding of the fundamental problems associated with fires and aim to inform strategies to prevent similar tragedies in the future.